Pentecostals in Hungary - Ungvari, Csaba (Budapest, Hungarian Pentecostal Church and Pentecostal Theological College, 2018)
This historical account of Pentecostals in Hungary is the first book of its kind to help English speaking readers and researchers more clearly understand the historical identity, activity, and role of Hungarian Pentecostalism within the larger world-wide Pentecostal family. The book parallels historical events happening within Hungary nationally with activity taking place on both the national and local levels of Pentecostal church life. The attention given to beliefs, practices, and attitudes throughout the book helps provide a structural framework to learn, evaluate, and understand the more than ninety-year history of Pentecostals in Hungary.
Includes references.